(untitled) (Research, Society and Development, 2025)
Systemic sclerosis (SSc) is a chronic autoimmune disease that, in addition to its physical manifestations, carries a profound psychological impact, affecting patients’ quality of life. Objective: This study aimed to conduct an integrative literature review to analyze the evidence on the intersection between the clinical manifestations of scleroderma and psychological aspects, such as depression, anxiety, and body image perception. Methodology: An integrative review was conducted in the PubMed, SciELO, and LILACS databases, following PRISMA recommendations. Eight studies published between 2021 and 2025 were selected, including systematic reviews, cohorts, clinical trials, and a meta-analysis, which addressed the relationship between psychological symptoms and the clinical progression of the disease. Results: The analyzed studies demonstrated a high prevalence of depression and anxiety in patients with SSc, often associated with clinical manifestations such as dyspnea, pain, and gastrointestinal symptoms. Factors like body image dissatisfaction, low access to mental health services, and the overlap of multiple symptoms (physical and emotional) were identified as significant determinants for a decline in quality of life and relational well-being. Conclusion: The evidence reinforces that care for individuals with systemic sclerosis must be integrated and multiprofessional, extending beyond the treatment of physical symptoms. The incorporation of psychological support strategies, mental health screening, and interventions focused on psychosocial adaptation is fundamental to promoting well-being and improving the quality of life for these patients.